Galectin 3 rs4644 gene polymorphism is associated with metabolic traits in Serbian adolescent population - Vidovic, Vanja; Novaković, Ivana; Damnjanović, Tatjana; Radić Savić, Žana; Vidović, Stojko; Škrbić, Ranko; Maksimović, Nela (Journal of Medical Biochemistry, 2023)
Background: Among many genes which have been analyzed to understand obesity and related metabolic traits among children and adolescents, not many studies are conducted on LGALS3 gene, especially in population of children. A positive correlation of circulating galectin 3 serum levels with impaired blood glucose, high blood pressure and higher values of serum lipids and was found in general population. The aim was to investigate possible association of rs4644 with body mass index, glycaemia, and lipid profile in Serbian adolescents. Methods: The study included 72 boys and 79 girls, 14-15 years of age. Among boys 51 (67.1%) had normal values of BMI, 11 (14.5%) were overweight, and 14 (18.4%) were obese. Among girls, 53 (63.9%) had normal BMI, 16 (19.3%) were overweight, and  14 (16.9%) were obese. Diabetes type 1 or 2, genetic syndromes, generalized inflammation, cardiovascular and malignant diseases were criteria for exclusion. Genotyping was performed by Real time PCR. Results: Girls carriers of CC genotype had statistically higher mean values of BMI, and triglycerides in comparison to the girls carriers of CA+AA genotypes, p=0.041, and p=0.045, respectively. The higher frequency of obese was found among group of girls who were carriers of CC genotype, p=0.049. No statistically significant association was observed among other analyzed parameters in neither examined groups. Conclusion: Our research indicates that there is an association between the CC genotype of rs4644 polymorphism with obesity and higher triglycerides level in the group of female adolescents.
Keywords: LGALS3; rs4644; lipid profile; BMI